2010
DOI: 10.1061/(asce)0887-3801(2010)24:1(25)
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Model and Exchange Object Concepts for Implementation of National BIM Standards

Abstract: The industry foundation class ͑IFC͒ standard building model schema is a necessary but not sufficient condition for achieving full interoperability between building information modeling ͑BIM͒ tools. Unless each information exchange within construction project workflows has its specific contents and level of detail defined, the breadth and flexibility of the IFC schema leaves room for errors. The national BIM standard approach for resolving the ambiguities of information exchange is based on "use cases," which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(119 citation statements)
references
References 10 publications
0
115
0
4
Order By: Relevance
“…Rule--based checking in BIM has been widely studied and developed by, among many others, Charles M. Eastman (Eastman et al, 2009(Eastman et al, , 2010Zhang et al, 2012). In their paper titled Automatic Rule--Based Checking of Building Designs (2009), Eastman et al provide a thorough survey of both the technology and structure of several IFC--based rule--checking efforts.…”
Section: Background Surveymentioning
confidence: 99%
“…Rule--based checking in BIM has been widely studied and developed by, among many others, Charles M. Eastman (Eastman et al, 2009(Eastman et al, , 2010Zhang et al, 2012). In their paper titled Automatic Rule--Based Checking of Building Designs (2009), Eastman et al provide a thorough survey of both the technology and structure of several IFC--based rule--checking efforts.…”
Section: Background Surveymentioning
confidence: 99%
“…Lee (2008) checked that it is possible to control construction info through BIM by applying info process to the project of apartments from proposing the process for BIM application in stages of design, building, and maintenance. Eastman et al (2010) suggested a data conversion system for compatibility of figure info between the IFC file system and the US BIM standard system to smooth info sharing through BIM models. Also, Liu and Issa (2012) examined plans for smooth info compatibility between BIM model info and info of the maintenance system so as to apply the BIM model info to the maintenance system for heightening the availability of BIM of the design stage in the maintenance stage.…”
Section: B Building Information Modelingmentioning
confidence: 99%
“…For example, the National BIM standard approach, well suited to the construction of new buildings, uses groups of experts in AEC to specify use-cases in what they call "Information Delivery Manuals" (IDMs). These IDMs serve as a basis to create specifics import and export translators to facilitate collaboration between design and construction stakeholders (Eastman et al, 2010); -Assisting the redesign of existing buildings, especially to the degree befalling France at time of writing, is less of a concern to BIM than assisting the design of new buildings allowing leeway for redesign later in the lifecycle; -More importantly to us, BIM software is currently incompatible with design approaches placing user involvement at their core such as participatory design, and is therefore of limited interest to user-centered architectural redesign.…”
Section: Plm and Building Information Modelingmentioning
confidence: 99%